OPTIMISM IN PATIENTS SURVIVOR CANCER - Uthomah, Laila; Lova Riza, Wina; Kuraesin, Uning (International Journal of Psychosocial Rehabilitation, 2020)
In the current millennial era, the pattern of human life is not like the time before the millennial era. The environment is full of pollution, fast food, unhealthy lifestyles, the number of hours of sleep that is not fair and the demands of work do humans prioritize the results obtained rather than the process to get it. One impact was seen by health problems, namely cancer. Cancer is a deadly stigma when someone listens to it. But some people can see cancer as part of the life process that must be passed. This understanding can be explained in the concept of optimism so that researchers are interested in seeing the phenomenon of the concept of optimism in cancer patients. This research uses a qualitative method with a phenomenological design and data collection is carried out intensively, deeply, and comprehensively. Data collection is done by interview, observation, and official documents. With this specific research, it can only be experienced by the subject under study and does not apply to other subjects. Two people who became the subject were visited by researchers when the subject was running therapy at one of the therapy sites in Bandung. The instrument used for data collection is humans, the researchers themselves. Data analysis activity begins with data collection, personalization, and creating units of meaning to get a textural description. The results showed that the two subjects displayed different optimisms. The behavior displayed by the NR subject showed pessimism in dealing with health after cancer diagnosis and treatment. While LL subjects showed themselves optimistic in facing health after cancer diagnosis and treatment.